1997
DOI: 10.1159/000026471
|View full text |Cite
|
Sign up to set email alerts
|

Greater Metabolic Rate Decreases in Hippocampal Formation and Proisocortex than in Neocortex in Alzheimer’s Disease

Abstract: Neuropathological studies of Alzheimer’s disease (AD) have found pathological changes in some cytoarchitectural regions and relative sparing in others. Positron emission tomography (PET) studies have also shown selective decreases in glucose metabolic rates but have generally focused on whole brain lobes or geometrically derived regions of interest. In this report, a template of Brodmann areas, derived from a whole brain histological section atlas, was used to analyze PET findings from 34 AD patients and 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…This discrepancy may reflect methodological differences because the studies cited above investigated patients in a resting condition, whereas the SVLT used in our study does not particularly address parietal lobe functions such as visuospatial processing. That neither the activity in the sensorimotor cortex nor the activity in the primary visual association areas such as the posterior temporal gyri varied significantly between the diagnostic groups is consistent with earlier findings (e.g., Kessler et al 1991; for a review, see Stein et al 1998). However, significantly reduced sensorimotor cortex activity values were described by Haxby et al (1988) for the severely demented.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This discrepancy may reflect methodological differences because the studies cited above investigated patients in a resting condition, whereas the SVLT used in our study does not particularly address parietal lobe functions such as visuospatial processing. That neither the activity in the sensorimotor cortex nor the activity in the primary visual association areas such as the posterior temporal gyri varied significantly between the diagnostic groups is consistent with earlier findings (e.g., Kessler et al 1991; for a review, see Stein et al 1998). However, significantly reduced sensorimotor cortex activity values were described by Haxby et al (1988) for the severely demented.…”
Section: Discussionsupporting
confidence: 84%
“…Recent neuroimaging studies have demonstrated structural (Jobst et al 1992;Pantel et al 1997), spectroscopic (Lazeyras et al 1998), and functional (Mann et al 1992;Pearlson et al 1992;Siegel et al 1995; for reviews, see Santens and Petit 1997;Small and Leiter 1998) cerebral changes in AD. These changes strike primarily the temporal and parietal association cortices but generally extend to the frontal cortex with progression of the disease (Buchsbaum et al 1991;Haxby et al 1988;Mann et al 1992;Mielke et al 1994;Smith et al 1992;Stein et al 1998), especially with secondary depression (Hirono et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…These CMRgl reductions have been reported in the posterior cingulate, parietal, and temporal cortex, and in the frontal cortex and whole brain in more severely affected patients (1)(2)(3)(4)(5). Other studies have reported CMRgl reductions in anatomically well characterized hippocampal and entorhinal cortical regions of interest (6)(7)(8)(9)(10). The posterior cingulate cortex (PCC) and the neighboring precuneus are metabolically affected in the earliest clinical and preclinical stages of AD (4,11), and the primary visual cortex is relatively spared (4,11).…”
mentioning
confidence: 84%
“…From there, this process spreads to the entorhinal region, hippocampus and neocortex [106,135,137]. The heightened vulnerability of neurons in the entorhinal and association cortices has been related to their high expression level of somatodendritic dephosphorylated neurofilament protein [138,139] or to their close synaptic relationship with limbic areas [140]. Other factors discussed in the context of the selective neuronal vulnerability in AD comprise, among others, early region-specific alterations in the blood-brain barrier [141], high gene expression of mitochondrial DNA-encoded ND4 (a subunit of complex I of oxidative phosphorylation) [142], a low portion of L-amyloid β precursor protein (L-APP, the APP obtained from mRNAs lacking exon 15 of the APP gene by alternative splicing in the presence of a high APP content) [143], a decrease in some glutamate receptor subunits expression (particularly GluR2/3) with concomitant alterations of calcium conductance through AMPA-selective channels and destabilization of intracellular calcium homeostasis [144], a mutation early in development (blastocyst stage or before) in a mDNA molecule and/or in the nDNA of the precursor cells of neurons later involved in AD, that impairs oxidative phosphorylation and increases production of superoxide radical and H 2 O 2 [145], or the particular vulnerability of brain regions that show accelerated progression during primate evolution [146,147].…”
Section: Accumulation Of Ndna Damage or Neuron Loss: Implications Formentioning
confidence: 99%